Parental media monitoring, prosocial violent media exposure, and adolescents' prosocial and aggressive behaviors. Issue 6 (25th August 2019) - Holmgren, Hailey G.; Padilla‐Walker, Laura M.; Stockdale, Laura A.; Coyne, Sarah M.
Abstract: Prosocial violent media (e.g., media that combines both violent and prosocial content) is especially popular in entertainment media today. However, it remains unclear how parental media monitoring is associated with exposure to prosocial violent content and adolescent behavior. Accordingly, 1, 193 adolescents were asked about parental media monitoring, media content exposure, and behavior. Main findings suggest that autonomy supportive restrictive monitoring was associated with lower levels of exposure to prosocial violent content, but only among older adolescents. Additionally, autonomy supportive restrictive monitoring was the only form of parental media monitoring associated with lower levels of violent content and higher levels of prosocial content, and autonomy supportive active monitoring was the only parental monitoring strategy that promoted prosocial behavior via exposure to prosocial media content. Discussion focuses on the importance of autonomy supportive parental monitoring, as well as the implications of parents encouraging their children to watch media with limited violent content—even if it is prosocial violent content.